Answer:
ln(2) + 3ln(a) - 4ln (b)
Step-by-step explanation:
ln(2a^3 /b^4)
We know that ln(x/y) = ln (x) - ln y
ln(2a^3 ) - ln (b^4)
We know that ln (xy) = ln x + ln y
ln(2) + ln(a^3 ) - ln (b^4)
We know that ln(x^y) = y ln (x)
ln(2) + 3ln(a) - 4ln (b)
Answer:
A.
Step-by-step explanation:
Slope = y2-y1/x2-x1
(2,-4) = (x1,y1)
(4,2) = (x2,y2)
Slope = (2+4)/(4-2)
= 6/2
= 3
Y=mx+b [Plugging (4,2) into this]
2 = 3×4 +b
2 = 12 + b
b = -10
79.35 divided by 5 equals: <u><em>15.87</em></u>
<em>~~~~~~~~~~~~~~~~~~~~~~~~~~~</em>
To check:
243
15.87
<span><u> x 5.00</u>
</span> 0000
<u> 0000</u>
79.35
<em>~~~~~~~~~~~~~~~~~~~~~~~~~~~~</em>
Hope this helped! :)
<span><em>Any more questions, please ask! :)</em></span>
4,000×0.035×2=280
.................